Using the Modified Apical Access Technique to Treat Peri-Implant Mucosa Defects: Description of the Technique and Three-Dimensional Quantitative Measurement of Buccal Augmented Tissue - Norberto Quispe-López; Tiago Marques; Yasmina Guadilla; Javier Flores-Fraile; Pablo Garrido-Martínez; Javier Montero (MDPI AG, 2024)
The importance of augmenting the peri-implant soft- and hard-tissue architecture is now widely accepted. However, while most contemporary research supports this premise, clinicians are encountering peri-implant soft tissue defects with increasing frequency, which they are therefore required to reconstruct. These complications can result from the difficulty of establishing an appropriate diagnosis and treatment plan or from suboptimal clinical situations (implant malposition, insufficient vestibular alveolar bone thickness or inadequate mucosal thickness). In this context, it is the peri-implant soft-tissue phenotype that most influences esthetic and health-related results in the short and long term. This article describes two clinical cases in which a modification of the apical access technique is presented that may be useful in clinical scenarios requiring large gains in mucosal thickness. Use of the modified bilaminar apical access with de-epithelialized free gingival graft technique showed promising results, with a significant increase in mucosal thickness and satisfactory outcomes in esthetics and peri-implant health.